Tribals and Dalits in Orissa : towards a social history of exclusion, c. 1800-1950 - Pati, Biswamoy (Oxford scholarship online, 2021)
This text examines diverse aspects of the social history of the marginalized sections of society in Orissa, focusing on the problems of colonialism and the way it impacted the lives of tribals, outcastes and dalits. It delineates how these socially excluded sections were terrorized and further impoverished by both the colonial government and the chiefs of the despotic princely states who worked in tandem with them. In course of six tightly argued chapters, Biswamoy Pati studies several key issues including 'colonial knowledge' systems which had a long afterlife, such as the stereotyping of tribals as violent and brutal and colonial constructions of the 'criminal tribe'.